Constraints on Relativistic Jets from the Fast X-Ray Transient 210423 Using Prompt Radio Follow-up Observations - Dina Ibrahimzade; R. Margutti; J. S. Bright; P. Blanchard; K. Paterson; D. Lin; H. Sears; A. Polzin; I. Andreoni; G. Schroeder; K. D. Alexander; E. Berger; et al. (The Astrophysical Journal)
Fast X-ray transients (FXTs) are a new observational class of phenomena with no clear physical origin. This is at least partially a consequence of limited multiwavelength follow-up of this class of transients in real time. Here we present deep optical ( g - and i -band) photometry with Keck, and prompt radio observations with the Very Large Array of FXT 210423 obtained at δ t ≈ 14–36 days since the X-ray trigger. We use these multiband observations, combined with publicly available data sets, to constrain the presence and physical properties of on-axis and off-axis relativistic jets such as those that can be launched by neutron star mergers and tidal disruption events, which are among the proposed theoretical scenarios of FXTs. Considering a wide range of possible redshifts z ≤ 3.5, circumstellar medium density n = 10 ^−6 –10 ^−1 cm ^−3 , and isotropic-equivalent jet kinetic energy E _k _,iso = 10 ^48 –10 ^55 erg, we find that we can rule out wide jets with opening angle θ _j = 15° viewed within 10° off-axis. For more collimated jets ( θ _j = 3°) we can only rule out on-axis ( θ _obs = 0°) orientations. This study highlights the constraining power of prompt multiwavelength observations of FXTs discovered in real time by current (e.g., Einstein Probe) and future facilities.